(untitled) (LEARNing Landscapes, 2018)
Education is a human endeavor, yet its research often prioritizes empirical knowledge while marginalizing human aspects of the educative experience. Creating space for self has the capacity to foster wholeness where there is disconnectedness and, therein, challenge academic conventions that prioritize dehumanization. Situated within post-qualitative inquiry and drawing on autobiography, I invite students to explore with me premises gleaned from Palmer’s work on identity and integrity. While we explicitly seek to explore how including autobiographical tenets can overcome practices that limit integrated ways of knowing, we also implicitly seek to legitimate the element of selfhood in our education contexts.